Elatostema bioppositum (Urticaceae), a new species from Guangxi, China (Bangladesh Journal of Plant Taxonomy, 2013)
A new species of Elatostema J. R. Forst. & G. Forst. (Urticaceae), E. bioppositum L.D. Duan & Y. Lin, is described and illustrated from Guangxi, China. This species was found growing in evergreen broad-leaved forests in limestone hills at altitudes of 410-550 m. The new species is related to E. oppositum Q. Lin & Y. M. Shui, but differs from the latter by stipule linear, lanceolate-linear or lanceolate, 12-25 mm long, 2.0-4.5 mm wide; leaf blade green after drying; male inflorescence 15-30 mm in diameter and peduncle 2-3 mm long; and female inflorescence 7-15 mm in diameter.DOI: http://dx.doi.org/10.3329/bjpt.v20i2.17392Bangladesh J. Plant Taxon. 20(2): 179-183, 2013